Boronic Acid Catalysis for Aza-Piancatelli Rearrangement - Tang, Wu-Bang; Cao, Kou-Sen; Meng, Shan-Shui; Zheng, Wen-Hua (Synthesis, 2017)
A first example of boronic acid catalyzed intermolecular aza-Piancatelli rearrangement to access a wide range of trans-4,5-disubstituted cyclopentenones is described. The catalytic system can also be extended to intramolecular aza-Piancatelli rearrangement to afford a wide range of azaspirocycles. Good to excellent yields were obtained in an excellent diastereoselective manner.
Keywords: boronic acid; aza-Piancatelli rearrangement; furylcarbinols; cyclopentenones; azaspirocycles